TANGGUNG JAWAB PT. JASARAHARJA PUTERA PEKANBARU TERHADAP GANTI RUGI ASURANSI PADA PENGANGKUTAN BARANG MELALUI JALUR LAUT BERDASARKAN UNDANG-UNDANG NOMOR 40 TAHUN 2014 TENTANG PERASURANSIAN - Githa Fitria Lisa Ulfa; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Carriage of goods by sea is a process of loading the goods into the ship , carrying goods from the loading point to the destination , and drop off the goods from ships to a specified place . Therefore, the transportation of insurance held by the shippers ( shipper ) as outlined in the agreement ( policy ) , so that the rights and obligations arising therein , in this case , namely the right to shippers ( shipper ) to claim the goods are damaged , missing. Transport insurance is often called marine insurance ( marine ) for marine insurance is the oldest form of insurance . Its history is closely related to shipping and trade , as well as its development . Without marine insurance , commerce would be severely hampered progress. In section 1367 Book of the Law of Civil Law (KUHPerdata) , hereinafter called the Civil Code states that a person is not only responsible for damages caused by his own actions , but also for any damages resulting actions of people who become dependents or caused by the goods that are under supervision. Responsibility PT. Jasaraharja Putera Pekanbaru in the settlement of compensation to the customer is still not appropriate to fulfill the agreement as a protection or assurance of terjdinya a peritiwa not certain which will be suffered by the customer. Barriers faced by PT . Jasaraharja Putera Pekanbaru in implementing the settlement of insurance claims carriage of goods by sea , namely : the amount of funds needed for adjusters and surveyors ; location or the location is relatively remote loss ; differences in fact between the policy conditions with the real situation ; lack of document / lack of documents claim ; and supporting documents and the loss of the goods at the time of the incident so difficult to calculate the lossKey Words: Legal Responsibility-Insurance-Indemnity